Determinants and Socio-Economic Impacts of Nurse Migration: Evidence from Migrant Healthcare Professionals (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The migration of nurses is a critical phenomenon with significant implications for both the source country and destination countries. This study explores the socio-economic conditions of migrant nurses and investigates the factor influencing their decision to migrate. The objective of the study is: To understand socio economic condition of migrant nurses and to find out the reason for preferring the destination and problem faced there. The study based on primary data collected from 50 nurses who working abroad. The research employs convenient sampling method by distributing a structured questionnaire through telephone. The findings highlight the primary challenges faced by migrant nurses, including cultural adjustment, professional integration and economic stability. Additionally, the study reveals that migration was preferred most of the nurses for career advancement and financial outcome and, more than one single push or pull factor is involved in migration. The analysis revels that better career opportunity, higher salary, and improved living conditions are the main drivers for migration. The study aims to provide a comprehensive understanding of the migration dynamics of nurses, contributing to policy discussions and managing and supporting migrant healthcare professionals. The study concluded that migration of nurses is necessary for professional growth of nurses and to achieve career advancement.